A springtime olympics demands special consideration for allergic athletes - Katelaris, C. H.; Carrozzi, F. M.; Burke, T. V.; Byth, K. (Journal of Allergy and Clinical Immunology, 2000)
BACKGROUND: The Sydney Olympic and Paralympic Games will be held in September-October 2000, which is early to mid-spring in the southern hemisphere. Pollen-sensitive athletes may encounter problems with allergic symptoms triggered by pollen exposure, thus compromising their ability to attain peak performance. OBJECTIVE: We sought to monitor pollen levels at the major Olympic venues to provide information for allergic athletes and their team doctors in order to adequately prepare them for Olympic competition. METHODS: We performed aerobiologic monitoring of the major Olympic venues to provide a profile of the most prevalent pollen species appearing during the spring. In the second part of this study, we surveyed a population of elite Australian athletes from Olympic sports to ascertain the prevalence of allergic rhinoconjunctivitis, to investigate the major allergens involved in sensitization, and to conduct a pilot study to assess the effect of allergic rhinoconjunctivitis on quality of life. RESULTS: The pollen counts obtained at the 3 major sites were high over the period of Olympic competition. Tree pollens appeared from July, and grasses appeared from early September and peaked in the second week of October, the beginning of Paralympic competition. A relatively small number of pollen varieties comprise the majority of the total pollen count. Two hundred fourteen athletes (61% male; mean age, 21 +/- 16 years) representing 12 Olympic sports participated in the study. Fifty-six percent gave a symptom history consistent with allergic rhinoconjunctivitis, 41% had symptoms of allergic rhinoconjunctivitis and a positive test response to any one allergen, and 29% had seasonal allergic rhinoconjunctivitis (a positive history and at least one positive skin prick test response to a seasonal allergen). Athletes from aquatic sports were more likely to have symptoms than those from other sports. Symptom scores were higher and quality of life ratings were poorer in allergic compared with nonallergic athletes over the spring period. CONCLUSION: Olympic team managers and medical officers need to adequately prepare Olympic athletes for the possibility of exposure to high pollen levels in the weeks leading up to this most important sporting event. Symptoms of pollen sensitivity, such as rhinoconjunctivitis and exacerbation of asthma, could be devastating to athletes expecting peak performance. Potential Olympic athletes should be screened for the possibility of pollen allergy and have medical programs with permitted medication tailored to meet their needs. This may involve preventative therapy with medication, such as intranasal corticosteroid sprays or immunotherapy programs, if symptoms are particularly severe. The newer nonsedating antihistamines are the treatment of choice for acute intermittent symptoms. Appropriate management will ensure that the allergic athlete will safely perform to maximum ability with permitted medication during the Spring 2000 Olympic Games in Sydney.